Cultural imperialism and popular culture: unveiling the influence of Salmah Ismail @ Saloma in the Federation of Malaya - Mohd Firdaus Abdullah,; Arba’iyah Mohd Noor,; Wan Hasmah Wan Teh,; Mohd Amir Mohd Zahari, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Salmah Ismail @ Saloma has been greatly influenced by imperialism, which led her to achieve such a fame in Federation of Malaya and also in the neighbouring countries. The influence of imperialism on the development of her career as an artist seems to be unnoticed even by Saloma herself and previous studies on her only conclude that Saloma was merely a singer with a melodious voice, actress, fashion icon, and a wife to a renowned artist, P. Ramlee. Cultural imperialism in Malaya is deemed to have influenced Saloma until she sparks the birth of popular culture in the Federation of Malaya. Therefore, this research would scrutinise the extent to which cultural imperialism in the Federation of Malaya has influenced Saloma in shaping popular culture in the country from the colonialism era until the post-independence era in the Federated Malay States. The results of this research show that Saloma had certainly brought a dominant image of imperialism in Malaya through culture imperialism. Saloma has successfully introduced a popular culture in the Federation of Malaya through her sense of music, media and fashion, and lifestyle. The finding of this study contributes significantly to the history of our country in relation to how the contribution of artists, which in this context referring to Saloma, had given an impact on our country's civilization. The findings of the current study can be used as a guide to highlight the role and contribution of artists that is less recognized in the civilization and history of the country.